2018
DOI: 10.1002/ccd.27580
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety, and patient satisfaction of same‐day discharge following peripheral arterial interventions: A randomized controlled study

Abstract: This small, single-center randomized study found that among carefully selected peripheral arterial interventions, SD may be feasible and safe. However, patient satisfaction and perceived safety were significantly lower among SD compared to the OS condition. Larger prospective studies are warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Recently, a single centre randomised clinical trial including 19 patients assessed the safety of same day discharge vs. overnight stays following peripheral arterial interventions but Islam et al did not evaluate the costs of the procedure. 8 The goal of the AMBUVASC randomised controlled trial was to assess the cost effectiveness of outpatient compared with inpatient hospitalisation for endovascular repair for LEAD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a single centre randomised clinical trial including 19 patients assessed the safety of same day discharge vs. overnight stays following peripheral arterial interventions but Islam et al did not evaluate the costs of the procedure. 8 The goal of the AMBUVASC randomised controlled trial was to assess the cost effectiveness of outpatient compared with inpatient hospitalisation for endovascular repair for LEAD.…”
Section: Introductionmentioning
confidence: 99%
“…This tool serves as a convenient and fairly universal way to assess any treatment method with the maximum accuracy of the estimated values. 2932 Using 5-point Likert scale instrument, Thors et al, reported high satisfaction in 100% of patients after endovascular treatment for PCS. 33…”
Section: Discussionmentioning
confidence: 99%
“…This tool serves as a convenient and fairly universal way to assess any treatment method with the maximum accuracy of the estimated values. [29][30][31][32] Using 5-point Likert scale instrument, Thors et al, reported high satisfaction in 100% of patients after endovascular treatment for PCS. 33 In the present study, the authors focused the attention of patients only on assessing the outcomes of endovascular embolization and endoscopic resection of the gonadal veins for treating PeVD.…”
Section: Patients' Satisfaction With Treatment At Month 6 After Inter...mentioning
confidence: 99%
“…We read with great interest the article by Islam et al . The authors should be congratulated for this well‐conducted and timely trial.…”
mentioning
confidence: 96%